Ethics and deontology of medical education and nurses in Portugual - Clara Costa Oliveira; Maria Conceição Azevedo (Editora da Universidade de Santa Cruz do Sul, 2012)
This article discusses deontological issues of health care professions in relation to their ethical foundation. We present four models of teaching ethics and deontology in doctors' training and the results of a PhD research on the teaching of these subjects in nurses' training in Portugal. Given the importance of bioethics in deontological training of health care professions, we present a comparative analysis of. bioethical principles enunciated by Beauchamp and Childress (1979), related to 'ethics of justice', and Kemp's(2000) proposal, associated to an 'ethics of care'. Given the ambiguity of these bioethical expressions, we focus on the analysis of its contents and the need to discuss the fundamentals of ethical training of doctors and nurses in relation to the ethical theories they are derived from. Utilitarian ethics, duty ethics, virtue ethics, when the analysis of bioethics' fundaments is not trained, the duty of caring of suffering can be put at risk. Abstract Abordaremos a deontologia de profissões de saúde (médicos e enfermeiros), relacionando-a com os seus fundamentos éticos. Apresentamos quatro modelos de ensino da ética e deontologia na formação dos médicos, e os resultados da pesquisa de doutorado sobre o ensino dessas disciplinas na formação de enfermeiros em Portugal. Dada a importância da bioética na formação desses profissionais, explicitam-se duas orientações fundamentais neste campo: os princípios bioéticos enunciados por Beauchamp e Childress(1979), relacionados com uma 'ética da justiça', e a proposta de Kemp(2000), próxima de uma 'ética do cuidado'. Dada a ambiguidade dos termos 'ética da justiça' e 'ética do cuidado', detemo-nos na análise de seu conteúdo e na necessidade de discutir os fundamentos da formação ética de médicos e enfermeiros, reportando-os às concepções éticas de que se derivam: ética utilitarista, ética do dever, ética da virtude. Indicaremos algumas repercussões da ausência de fundamentação ética na função cuidadora destes profissionais.